Fundamentals of Entrepreneurship (ENT300) : Green Heart sport centre / Benedict Russell Anar Robert Asai … [et al.] - Robert Asai, Benedict Russell Anar; Dominic Ahoi, Denicca; Iba, Kenny Sigat; Ripat Eric, Oldrige; Jimmy, Sonia (2011)
The name of our company is Green Heart Sport Centre. The business is in form of enterprise which consists of five members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is providing the service throughout facilities and equipment as well as the expert trainers to the customer. We do provide the futsal court, badminton court and gym which facilitate by the instructor. The customer will be able assist by the instructor ifthey are not clear with uses of equipment and the rule ofthe sport centre.